ANALYSIS OF USER SATISFACTION OF THE GOPAY FINTECH APPLICATION IN ADOLESCENTS IN DENPASAR USING IS SUCCESS MODEL - Ni Kadek Rahayu Widiani; Ni Made Estiyanti; Helmy Syakh Alam (LPPM STMIK Pringsewu, 2022)
This study aims to analyze how much trust and satisfaction of adolescent Gopay Fintech users in Denpasar city by using the Delone & McLean IS Success Model. The data analysis method used is the SEM PLS method with the help of the Smart-PLS software version 3.0. This software is used to carry out testing starting from the validity and reliability test stages up to the overall data processing stage. The results of this study indicate that the accepted hypotheses. 1) The system quality variable has a positive and significant effect on trust, 2) the system quality variable has a positive and significant effect on user satisfaction, 3) the information quality variable has a positive and significant effect on trust, 4) the interface design quality variable has a positive and significant effect on trust, 5) the security variable has a positive and significant effect on trust, 6) the security variable has a positive and significant effect on user satisfaction, 7) the trust variable has a positive and significant effect on user satisfaction. Then there are two rejected hypotheses. 1) The information quality variable has a positive effect but does not have a significant relationship to user satisfaction, and 2) the interface design quality variable has a positive effect but does not have a significant relationship to user satisfaction